Analysis of the School Principal's Leadership Strategies in Overcoming Human Resource Management Challenges (A Qualitative Case Study at SMA Public 1 Bonegunu, North Buton Regency, Southeast Sulawesi Province) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research investigates the leadership strategies employed by the principal in addressing human resource management (HRM) challenges at SMA Negeri 1 Bonegunu, located in North Buton Regency, Southeast Sulawesi Province. Utilizing a qualitative descriptive method, data were gathered through in-depth interviews, observations, and document reviews. The study involved the principal, teaching staff, and educational personnel as participants. The results reveal several key HRM challenges, including a shortage of teachers, low motivation levels, insufficient ongoing professional development, and resistance to change. In response, the principal implemented collaborative and transformational leadership approaches. These included promoting transparent communication, empowering teachers through internal mentoring, encouraging participatory decision-making, and building partnerships with both the education office and the school committee. These strategies have been effective in improving staff engagement and performance, even amidst constraints related to facilities and infrastructure. The study concludes with a recommendation to enhance principals' managerial capabilities and to support the development of educational policies that are responsive to local needs.